2022
DOI: 10.1039/d2ta04237a
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a novel heterostructure of NiSe2/CoSe2 nanoparticles with boosted sodium storage properties for sodium-ion batteries

Abstract: Sodium-ion batteries (SIBs) are one type of the most promising technologies for large-scale clean electricity energy storage and conversion. Developing SIBs anode materials, which are the major limitation in achieving...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…The two spin orbital peaks at 853.30/854.80 and 870.80/872.78 eV belong to the redox pair of Ni 2+ /Ni 3+ , attributing to Ni 2p 3/2 and Ni 2p 1/2 , respectively. [47] It is noteworthy that the peaks of 2p 3/2 of Ni 2+ of H-NiS/NiS 2 @C are located between the corresponding peaks of NiS@C and NiS 2 @C (NiS@C: 852.84 eV, H-NiS/NiS 2 @C: 853.30 eV, and NiS 2 @C: 853.78 eV), indicating that the charge of NiS in the H-NiS/NiS 2 @C may be transferred to the surface of NiS 2 . The strong electronic interaction between NiS and NiS 2 evokes charge redistribution and thus facilitates the improvement of the electronic structure of the H-NiS/NiS 2 @C. [48] In the S 2p spectra, there are four types of core-level peaks of S 2p for H-NiS/NiS 2 @C, NiS@C, and NiS 2 @C (Figure 3e), corresponding to S 2− , (S 2 ) 2− , C-S, and S-O bonds, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The two spin orbital peaks at 853.30/854.80 and 870.80/872.78 eV belong to the redox pair of Ni 2+ /Ni 3+ , attributing to Ni 2p 3/2 and Ni 2p 1/2 , respectively. [47] It is noteworthy that the peaks of 2p 3/2 of Ni 2+ of H-NiS/NiS 2 @C are located between the corresponding peaks of NiS@C and NiS 2 @C (NiS@C: 852.84 eV, H-NiS/NiS 2 @C: 853.30 eV, and NiS 2 @C: 853.78 eV), indicating that the charge of NiS in the H-NiS/NiS 2 @C may be transferred to the surface of NiS 2 . The strong electronic interaction between NiS and NiS 2 evokes charge redistribution and thus facilitates the improvement of the electronic structure of the H-NiS/NiS 2 @C. [48] In the S 2p spectra, there are four types of core-level peaks of S 2p for H-NiS/NiS 2 @C, NiS@C, and NiS 2 @C (Figure 3e), corresponding to S 2− , (S 2 ) 2− , C-S, and S-O bonds, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…6 b) [ 30 , 32 ]. To be more specific, the capacitive contribution at various scan rates can be verified by the following equation [ 56 , 57 ]: where k 1 v represents the contribution from capacitive behaviors, while k 2 v 1/2 corresponds to the contribution from diffusion [ 56 , 57 ]. As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 6 f, the lower R ct values in ether-based electrolyte indicate rapid charge transfer and stable interface [ 56 ]. For the ester-based electrolyte, the R ct value increases significantly from 34.6 (1st cycle) to 93.5 Ω (50th cycle), which can be attributed to the formation of a thick and unstable SEI layer caused by the ester-based electrolyte and then slow down the interfacial kinetics [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the XRD pattern of the NiSe 2 /NC hybrid spheres, it is revealed that the main phase is NiSe 2 with distinct peaks at 30.1, 33.8, 37.0, and 50.9° belonging to the (200), (210), (211), and (311) planes of cubic NiSe 2 (JCPDS no. 88-1711), accompanied by a weak and broad peak originating from the amorphous carbon species. This result confirms that all the Ni species in Ni/NC spheres have been completely converted into NiSe 2 with highly crystalline features during the selenization treatment.…”
Section: Resultsmentioning
confidence: 99%